Evaluation of Tomato Hybrids Carrying Ty‐1 and Ty‐2 Loci to Japanese Monopartite Begomovirus Species. Issue 3 (5th November 2012) - Shahid, Muhammad Shafiq; Ito, Takuya; Kimbara, Junji; Onozato, Ayumu; Natsuaki, Keiko T.; Ikegami, Masato
Abstract Tobacco leaf curl Japan virus, Honeysuckle yellow vein mosaic virus and Tomato yellow leaf curl virus are three begomoviruses that infect tomato crops in Japan. Tomato infection by begomoviruses has increased in Japan after the development of a high level of resistance to certain insecticides in some populations of the vector B. tabaci biotypes 'B and Q'. Ty‐1 and Ty‐2 homozygous tomato hybrids were evaluated for reaction to monopartite begomovirus species in Japan by Agrobacterium‐mediated inoculation. Test plants were evaluated by a disease assessment scale (DAS), varying from 1 = no symptoms to 4 = severe symptoms, and systemic infection was evaluated by polymerase chain reaction (PCR), using specific begomovirus primers for each virus. Ty‐1 hybrids showed tolerance to HYVMV and with a large number of plants being neither virus‐free nor symptom‐free. The response of Ty‐1 hybrids was also resistant to moderately resistant against TbLCJV. The response of Ty‐2 hybrids was resistant to highly resistant against the three monopartite begomoviruses, when compared with susceptible plants.